THE EFFECT OF CAPITAL, LABOR, PRICE, AND PRODUCTION OF PALM OIL ON THE INCOME OF FARMERS (JURNAL ECONOMICA : Research of Economic And Economic Education, 2018)
This study aims to analyze 1) the effect of capital (X1) on the income of oil palm farmers in Koto Balingka District, West Pasaman Regency, 2) the influence of labor (X2) on the income of oil palm farmers in Koto Balingka District, West Pasaman Regency, 3) the influence of prices (X3) on the income of oil palm farmers in Koto Balingka District, West Pasaman Regency and 4) the effect of production (X4) on the income of oil palm farmers in Koto Balingka District, Pasaman Barat District. 5) Influence (X1), (X2) (X3), (X4) Taken together on the income of oil palm farmers in Koto Balingka District, West Pasaman Regency.                         Based on data obtained from the research results (1) Capital has a significant effect on the income of oil palm farmers (2) labor has a significant effect on the income of oil palm farmers (3) Prices have a significant effect on the income of oil palm farmers (4) Production has a significant effect on the income of oil palm farmers (5) Capital, Labor, Price and Production of palm oil simultaneously have a significant influence on the income of oil palm farmers.